EFEKTIVITAS SELF-HEALING TECHNIQUE SEBAGAI STRATEGI PENURUNAN STRES PADA PENDERITA AUTOIMMUNE DISEASE - Ros, Rosyida; Nisa, Chairun; Azzahra, Nadhila; Binqalbi Ruzain, Raihanatu (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2021)
Autoimmunity is a chronic disease that attacks healthy body tissues; there are more than 80 types of disease. Patients will experience physical function and psychological disorders such as stress. Psychological stress has been implicated in the development and severity of autoimmune diseases with a value of 50%. This study focused on treatment, including stress management and behavioral interventions to prevent stress-related immune imbalances. This study aims to determine the effectiveness of the self-healing technique in expressing writing and self-talk in reducing the stress level of autoimmune sufferers and in determining the level of social support received. The study was conducted 6-27 July 2021, week 1 expressing writing, week two self-talk, week three social support. The methods used a quantitative type of quasi-experimental design, matching pretest-posttest group design. The subjects were 30 patients, 15 patients in the control group and 15 patients in the experimental group. Data analysis used the paired-sample t-test and Wilcoxon test. The results showed that the experimental group experienced a decrease in stress levels than the control group (p-value = 0.001 < = 0.05). Social support affects patient stress. The conclusion is that giving expressing writing and self-talk therapy can reduce stress levels in autoimmune patients.